Dynamic Changes in Neutrophil Counts and Neutrophil Granular Protein Levels in Convalescent COVID-19 Patients - Rajamanickam, Anuradha; Kumar, Nathella Pavan; P, Arul Nancy; Selvaraj, Nandhini; Munisankar, Saravanan; Renji, Rachel Mariam; V, Vijayalakshmi; Murhekar, Manoj; Thangaraj, Jeromie Wesley Vivian; Kumar, Muthusamy Santhosh; Kumar, CP Girish; Bhatnagar, Tarun; et al. (Archives of Clinical and Biomedical Research, 2022)
Neutrophils play an important role in the pathophysiology of COVID-19. However, the dynamics of changes in neutrophil numbers and function in convalescent individuals of SARS-CoV2 infection has not been well explored. Hence, we aimed to determine absolute counts, percentages of neutrophils, Neutrophil-To-Lymphocyte Ratio (NLR) and the plasma levels of neutrophil elastase (NE), myeloperoxidase (MPO) and proteinase-3 (PTN-3) in seven groups of COVID-19 individuals, based on days since RT-PCR confirmation of SARS-CoV-2 infection. Our data demonstrated that both absolute counts and percentages of neutrophils, neutrophil-to-lymphocyte ratio (NLR), as well as the circulating levels of NE, MPO and PTN-3 decreased from Days 15-30 to Days 91-120 and plateaued thereafter. Severe COVID-19 patients exhibited increased levels of neutrophil counts and percentages, NL ratio and NE, MPO and PTN-3. Thus, our study provides an important insight into the kinetics of alterations in neutrophil counts, percentages, the NL ratio and the levels of neutrophil granular proteins in convalescent COVID-19 individuals.